PENGARUH PERENCANAAN BERBASIS DATA TERHADAP EFEKTIVITAS SEKOLAH DASAR NEGERI: TEMUAN EMPIRIS DI KECAMATAN SUKASARI - Tata Karwita; Taufani Chusnul Kurniatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of Data-Based Planning (DBP) on School Effectiveness in the context of implementing evidence-based education policies. Using a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, this study examines the structural relationship between DBP and school effectiveness through the distribution of questionnaires to all teachers in the Sukasari District of Purwakarta Regency. The results show that DBP has a very strong and significant effect on school effectiveness (β = 0.853, t = 22.466, p = 0.000), and demonstrates high predictive relevance as indicated by the Q²predict value of 0.707. These findings indicate that planning that incorporates problem identification, data-based reflection, and measurable program formulation can significantly enhance school management and performance effectiveness. Theoretically, this study strengthens the literature on data-driven decision making as the foundation for developing effective schools, while practically it highlights strategic implications for strengthening teachers’ data literacy in optimizing the Education Report (Rapor Pendidikan) and the IRB approach. This study provides an original contribution through strong empirical evidence regarding the role of DBP as a determinant of school effectiveness, although it still has limitations in terms of research context and variables examined. These findings open opportunities for further research to explore mediating or moderating variables and mixed-methods approaches to gain a more comprehensive understanding of DBP practices. Keywords: Data-Based Planning, School Effectiveness, PLS-SEM, educational management, data-driven decision making;